(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract. Today, artificial intelligence (AI) technologies are increasingly penetrating all aspects of our lives, particularly the education sector. This article discusses the software architecture of intelligent teaching systems, their components, and the possibilities of using AI models in the learning process. It highlights how adaptive learning, large language models (LLMs), and machine learning algorithms enable a personalized approach to students. The article also focuses on software architecture approaches that should be considered when designing AI-based educational systems.